Pricing Strategies for Offline and Online Consumers in Modern Business - Fandora, Karmila; Safira, Adhe Okta; Aulya, Vivi Rizky; Abror, Abror; Afdal, Zul (Academia Open, 2025)
General Background: The rapid expansion of digital platforms has reshaped consumer behavior and pricing strategies, creating distinct dynamics between online and offline markets. Specific Background: While e-commerce fosters impulsive and socially driven purchases influenced by dynamic and value-based pricing, offline markets remain tied to stable pricing and tangible shopping experiences. Knowledge Gap: Existing studies often analyze pricing strategies in isolation, lacking a comprehensive synthesis that bridges offline and online contexts within the modern omnichannel landscape. Aims: This study employs a Systematic Literature Review (SLR) of research published between 2021–2025 to identify effective pricing approaches for both consumer segments. Results: The review of 20 peer-reviewed articles highlights that dynamic pricing, value-based pricing, and Pay-What-You-Want (PWYW) are central strategies, with effectiveness moderated by consumer psychology, product attributes, and channel structures. Online consumers respond strongly to personalized, transparent, and flexible pricing, while offline consumers prioritize experiential value and price stability. Novelty: The study integrates theoretical and empirical insights into a unified framework that reveals the critical role of psychological factors, ethics, and digital transformation in shaping pricing effectiveness. Implications: Findings underscore the importance for businesses to design adaptive, technology-driven pricing strategies that harmonize offline and online channels while sustaining consumer trust and long-term competitiveness. Highlights: Online consumers are strongly influenced by dynamic pricing, social commerce, and impulsive buying Offline consumers rely on stable pricing and hands-on product experiences Omnichannel strategies demand price consistency across digital and physical channels Keywords :Dynamic Pricing, Consumer Behavior, Online Shopping, Offline Retail, Value-Based Pricing